2022
DOI: 10.3390/coatings12081045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Cooling Rate of Thermal Simulation on the Microstructure and Mechanical Properties of Low-Carbon Bainite Steel by Laser-Arc Hybrid Welding

Abstract: A new kind of low-carbon bainite steel with excellent strength and toughness was developed, serving as the bogie of the next-generation high-speed train. However, the softening of the heat-affected zone (HAZ) in laser-arc hybrid welding (LAHW) needs to be overcome. In this study, the effect of the cooling rate of the LAHW process on the microstructure and mechanical properties in the HAZ was explored via thermal simulation. The results showed that with increased cooling rate, the grain size increased, the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A previous study of hybrid welding on steel plates 4.8 mm thick showed that the cooling rate in the fusion zone was calculated as 20-83.3°C/sec [14]. In the case of another previous study of hybrid welding on steel plates 6 mm thick, the cooling rate in HAZ was 25-35°C/sec [15]. The cooling rate selected in this study seemed to be within these values.…”
Section: Charpy Impact Test Of Thermal Cycle Simulated Test Pieces 23...mentioning
confidence: 53%
“…A previous study of hybrid welding on steel plates 4.8 mm thick showed that the cooling rate in the fusion zone was calculated as 20-83.3°C/sec [14]. In the case of another previous study of hybrid welding on steel plates 6 mm thick, the cooling rate in HAZ was 25-35°C/sec [15]. The cooling rate selected in this study seemed to be within these values.…”
Section: Charpy Impact Test Of Thermal Cycle Simulated Test Pieces 23...mentioning
confidence: 53%
“…In contrast to the S355J2 + N and S690QL1, no LB/M but FS was found in GCHAZ. Therefore, a sufficient local C enrichment is present to form granular M/A microphases as found for linear welding [13]. A diffusion-controlled C segregation took place despite the higher cooling rates in DASW.…”
Section: Discussion and Deductionmentioning
confidence: 77%
“…Whereas, microalloyed steels bring great advantages in weldability due to their lower hardenability and grain growth hindering and thus forming mainly bainitic structure [7,9,10]. Additionally, martensite-austenite constituents (M/A) are formed depending on cooling rates [13]. However, these investigations mainly focus on linear arc welding processes with typical thermocycles and heat inputs causing larger cooling times of t 8/5 > 5 s. DASW implies a specific thermocycle with extremely high heating and fast cooling [14].…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the molten pool flow field, temperature field and stress field during the LC process is of great help in understanding the macroscopic morphology, microstructure evolution and properties control of LC. Many scholars simulated the molten pool flow behavior, temperature field, stress field and microstructure based on fluid dynamics and physical phase field process [18][19][20][21][22].…”
mentioning
confidence: 99%